Non-motor symptoms in patients with Spinocerebellar ataxia type 12 - Basu, Purba; Choudhury, Supriyo; Mondal, Siddhartha Sankar; Siddique, Ummatul; Rahman, Simin; Ganguly, Jacky; Mukherjee, Soumava; Singh, Nilam; Tiwari, Mona; Kumar, Hrishikesh (Frontiers in Neurology, 2024)
Introduction Spinocerebellar ataxia type 12 (SCA12) is a rare autosomal dominant neurodegenerative disorder caused by abnormal CAG repeat expansion in the PPP2R2B gene. This disease is classically characterized by action tremor, dysarthria, ataxia, and hyperreflexia. There are limited reports regarding the non-motor symptoms in patients with SCA 12. We investigated the frequency and factors associated with the selected non-motor symptoms in patients with SCA 12. Methods Genetically diagnosed (CAG repeats > 43) and symptomatic cases of SCA 12 were included in the study. Motor severity was assessed using the Scale for the Assessment and Rating of Ataxia (SARA) and The Essential Tremor Rating Assessment Scale (TETRAS). Non-motor symptoms such as depression, autonomic function, and cognition were assessed using the Hamilton Depression Rating Scale (HAM-D), the Scales for Outcomes in Parkinson's Disease-Autonomic Dysfunction (SCOPA-AUT), and the Montreal Cognitive Assessment (MoCA), respectively. Results The mean age of the cohort with 34 SCA12 patients was 64.87 years (standard deviation 6.844). In this study, 21 patients (61.76%) had either mild or moderate cognitive impairment, almost equally frequent in early and advanced cases. Similarly a number of patients demonstrated evidence of moderate and severe depression. The SARA score was strongly associated with the MoCA score, and CAG repeat length could independently predict the MoCA score in this cohort. Autonomic symptoms were commonly present, with the majority of the patients experiencing urinary symptoms. Discussion Non-motor symptoms are common in SCA12 patients, even in the early stages of the condition. Timely detection and treatment of these symptoms may improve the therapeutic outcome and quality of life for SCA12 patients. The diverse symptoms of SCA12 perhaps indicate a widespread neurodegeneration beyond the cerebellum or its direct connections.